Correction to: Acute heat-stress testing in coral bleaching research: a review of research using the Coral Bleaching Automated Stress System (CBASS) - Ilan E. Bubb; Kay Watty; Lyza Johnston; Verena Schoepf (Coral Reefs, 2026)

Acute heat-stress testing in coral bleaching research: a review of research using the Coral Bleaching Automated Stress System (CBASS) - Ilan E. Bubb; Kay Watty; Lyza Johnston; Verena Schoepf (Coral Reefs, 2026)
As climate change intensifies, identifying heat-resistant corals is essential for advancing coral‐bleaching research and informing reef conservation and restoration. The Coral Bleaching Automated Stress System (CBASS) is designed to meet this need by conducting acute heat-stress assays within a standardized methodological framework. Given its affordability and short duration, CBASS use has increased since 2020, warranting a first review of its application. Here, we assess (1) the scope of CBASS research including geographic and species representation, (2) variation in experimental design, (3) the range of measured response variables, and (4) how CBASS-derived heat responses compare with those from longer-duration experiments and in situ surveys. We then synthesize these findings to identify advantages and limitations and suggest improvements. We show that CBASS studies exhibit taxonomic and depth biases similar to other coral-bleaching experiments. Most studies include adequate biological replication but insufficient tank replication. Temperature treatments were highly standardized, whereas rationales for selecting light levels were lacking. Frequent tissue sloughing and mortality in the highest temperature treatment underscore the need to re-evaluate the use of extreme temperatures. Chlorophyll fluorescence and associated dose–response metrics such as ED50 were the most commonly measured response variables, but standardization and reporting warrant improvement. Notably, in-depth review of the few studies comparing acute and longer-duration stress assays indicates that it remains unresolved whether CBASS-derived coral responses reliably predict coral performance under real-world heatwave scenarios. Consequently, we caution relying solely on acute stress assays to inform reef conservation and genotype selection for restoration planning until further validation is achieved.

Using reflectance to measure chlorophyll a in corals: calibration and implications of skeletal optical properties - Kay Watty; Verena Schoepf; Kelly W. Johnson; Sophie Littke; Rene M. van der Zande (Coral Reefs, 2026)
Climate change-driven coral bleaching and associated chlorophyll (Chl) loss increasingly threaten coral reefs, highlighting the need for non-invasive, cost-effective tools to assess corals’ physiological condition. Researchers have explored the reflectance-based Normalized Difference Vegetation Index (NDVI) as a proxy for Chl a . However, almost no calibration curves exist to date; thus it remains unknown if the relationship between Chl a and NDVI differs among coral species, and whether it is influenced by skeletal optical properties. Here, we correlated Chl a content to NDVI in three coral species with different skeletal morphologies and reflectance modes across a range of health states (i.e., bleaching states). We found a strong positive relationship between Chl a and NDVI in all species, validating NDVI as a proxy for Chl a in corals. However, this relationship is non-linear, showing deviations at the highest and lowest ends of the pigmentation spectrum. We propose that in healthy states, this non-linearity is due to pigment self-shading, whereas in bleaching states, it is caused by backscattering of light by the increasingly exposed coral skeleton, because pigment loss enhances absorption by the remaining Chl a pigments and lowers, rather than increases, reflectance. To avoid Chl a under- or overestimation, we recommend to log-transform Chl a and create species-specific calibration curves. Overall, the non-invasive, repeatable, and scalable nature of reflectance measurements and NDVI make them valuable tools for assessing coral health both ex- and in situ. They provide a comprehensive view of the holobiont’s physiological condition and hold potential for broader applications in reef-scale monitoring, remote sensing, coral restoration, and conservation.